Simulation of standalone photovoltaics using PSPICE - Fong K.M.; Jalal T.S. (2023)
Photovoltaic or PV system in Malaysia is getting more important as Malaysia is taking a lead among the ASEAN countries in PV system. For example, Pusat Tenaga Malaysia through its Malaysian Building Integrated Photovoltaics (MBIPV) programme has recently launched the Solar1000 bidding to encourage PV usage at households. However, photovoltaics are still expensive as it is rather a new technology in Malaysia. The development of PV system is also expensive with expensive facilities required to fabricate solar cells. To save development cost, PV system can also be modelled using PSPICE. Given that PSPICE is a common simulation software among electrical engineering students, it is useful to be able to use it as a simulation tool. This paper demonstrates the simulation of a PV system. One of the two types of photovoltaic, which is a standalone system, will be focused on in this paper. Standalone PV systems are the most popular systems used worldwide despite the more recent interest of the market in grid-connected systems. A standalone PV system should provide enough energy to a totally mains-isolated application. This paper discusses common PV features such as peak solar hour (PSH) concept, loss of load probability (LLP) and long term plus system level simulation of a standalone PV system modeled and simulated using PSPICE. 2007 IEEE.